Crowdsourced digitisation of cultural heritage. A case-study into Wiki Loves Monuments. - Proost, Iljuschka (My University, 2017)
Wiki Loves Monuments is an online platform aimed at crowdsourcing photographs and information about build heritage from around the world. It enables pro-amateur users worldwide to participate in documenting heritage sites, while engaging them with a rewarding activity. The strength of Wiki Loves Monuments is the ability to bind thousands of people to contribute to enriching data about heritage with limited resources. Anyone with a smartphone could directly participate in the project. Trustworthiness is the main treat to Wiki Loves Monuments as online anonymous contributors do not have the traditional credentials needed to describe or catalogue heritage and history. Further external opportunities for Wiki Loves Monuments can be found in the heritage organisations that possess the knowledge to create notability and trustworthy information about heritage, this could help mitigate these problems.